Research progress on the effect of traditional Chinese medicine on the activation of PRRs-mediated NF-κB signaling pathway to inhibit influenza pneumonia - Zhang, Ling; Ye, Xiong; Liu, Yuntao; Zhang, Zhongde; Xia, Xueshan; Dong, Shuwei (Frontiers in Pharmacology, 2023)
Influenza pneumonia has challenged public health and social development. One of the hallmarks of severe influenza pneumonia is overproduction of pro-inflammatory cytokines and chemokines, which result from the continuous activation of intracellular signaling pathways, such as the NF-κB pathway, mediated by the interplay between viruses and host pattern recognition receptors (PRRs). It has been reported that traditional Chinese medicines (TCMs) can not only inhibit viral replication and inflammatory responses but also affect the expression of key components of PRRs and NF-κB signaling pathways. However, whether the antiviral and anti-inflammatory roles of TCM are related with its effects on NF-κB signaling pathway activated by PRRs remains unclear. Here, we reviewed the mechanism of PRRs-mediated activation of NF-κB signaling pathway following influenza virus infection and summarized the influence of anti-influenza TCMs on inflammatory responses and the PRRs/NF-κB signaling pathway, so as to provide better understanding of the mode of action of TCMs in the treatment of influenza pneumonia.